The Effectiveness of Digital Marketing Through TikTok in Increasing Brand Awareness and Customer Interaction in MSMEs in Yogyakarta (International Journal of Economics and Management Research, 2026)
The development of social media platforms like TikTok has transformed the way MSMEs interact with consumers. However, many businesses still struggle to build brand loyalty because digital promotions are ineffective and unable to fully drive consumer purchase intention. This phenomenon suggests that high promotional activity does not always align with increased customer trust and brand engagement. This study aims to analyze the influence of digital marketing strategies, influencer marketing, and purchase intention on brand loyalty among TikTok users in Yogyakarta. The study used a quantitative approach with a survey of 250 active TikTok users in Yogyakarta who had viewed MSME product promotions. Data were collected through an online questionnaire and analyzed using SPSS version 26 with validity and reliability tests, as well as multiple linear regression. The results showed that digital marketing strategies, influencer marketing, and purchase intention had a positive and significant influence on brand loyalty. These findings confirm that implementing innovative digital strategies and collaborating with credible influencers can increase purchase intention and strengthen customer loyalty to MSME brands on TikTok.